A qualitative study on effective distance language education: Advantages and challenges from the learners’ perspectives - BAŞKAN, NACİ SERHAT (My University, 2023)
The advent of digitalisation and the spread of online platforms have transformed the way educational materials are delivered, creating unprecedented learning opportunities. This innovative modality, capable of initiating a paradigm shift, enables students to obtain their education from virtually any location. The main objective of this research study is to investigate and assess the effectiveness of real-time online instruction in the German language. This appraisal includes the standard of instruction, the degree of interaction in the online milieu, and the deployment of Web 2.0 tools, all viewed from the learner\"s perspective. This research aims to elucidate the experiences and perceptions of students from diverse academic backgrounds who participated in the German language instruction course at a public university during the post-pandemic period. The syllabus was constructed with reference to content development models in distance education. Data collection for the study was achieved via an open-ended questionnaire and semi-structured interview forms. The study design is rooted in action research. The collected data were examined with the MAXQDA 2022 qualitative data analysis software. The research pinpointed three primary themes from the compiled data: structure related issues on distance education, effective communication in distance education, and viewpoints on Web 2.0 tools. These themes offer an extensive insight into the present scenario and potential future trajectory of online language education.Keywords: Distance learning, Web 2.0 tools, potentials, challenges, German language teaching, communication barriers
Keywords: Açık ve Uzaktan Öğrenme; Eğitim; Yabancı Diller Eğitimi; Open and Distance Learning; Education; Education in Foreign Languages; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities